The Correlation between SPeaking Anxiety and Students' Speaking Skill - navisah ummul khoir (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2019)
English speaking is an activity to produce some words to convince the opponents about our statement or thought. As an English skill, speaking cannot be separated from the problems which faced by the students. The problems such as fear of mistakes, shyness, lack of confidence, lack of motivation and anxiety. Among those problems, anxiety is the most crucial problem in speaking.Anxiety itself divided into three categories which are Trait Anxiety, State Anxiety and Specific-Situational Anxiety. The objective of this research was to find out whether there is any correlation between speaking anxiety and students’ speaking skill. This research was classified as a correlation research. The subject was 29 fourth semester students of English Department of Univerity of Islam Malang. The were two instruments for this research those are FLCAS questionnaire adopted from Howritz (1986) and Speaking test which used speaking scoring rubric. The result of this study showed that speaking anxiety and students’ speaking skill are perfectly negative correlated each others. The significant value is 0.00 which is less than 0.05 level. Then, The r value is -683 which means those two variables have a high negative correlation because the r value significant at point 0.60.